If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5(p+4)=p-(8-p)
We move all terms to the left:
-5(p+4)-(p-(8-p))=0
We add all the numbers together, and all the variables
-5(p+4)-(p-(-1p+8))=0
We multiply parentheses
-5p-(p-(-1p+8))-20=0
We calculate terms in parentheses: -(p-(-1p+8)), so:We get rid of parentheses
p-(-1p+8)
We get rid of parentheses
p+1p-8
We add all the numbers together, and all the variables
2p-8
Back to the equation:
-(2p-8)
-5p-2p+8-20=0
We add all the numbers together, and all the variables
-7p-12=0
We move all terms containing p to the left, all other terms to the right
-7p=12
p=12/-7
p=-1+5/7
| 40+85+x=180 | | 40+85+x=140 | | 1=7x−3(3x−7) | | -45+25=-5p+9p | | (7x-22)=8 | | 4(x+9)=-30 | | 4x+10+13x-5+56=180 | | 2(-4x)+6=40-8x | | (-x+3)6+3x=-3 | | 3x-5x-12=1x-88-5 | | 928n-7=(4-) | | 2x^2+26=20x | | 30=-10u-6+4u | | -90=-10-4n | | 14+28x=96 | | ⅙(7x-22)=8 | | -3(1+8n)=8n=23+2n | | -3(1-8n)=8n=23+2n | | 15d-30=150 | | f(-4)=8+4•-4 | | -19=9x+8 | | 2a+4=-16 | | 3(4x+2)+4=6(2x-4)+8 | | -7k-8k=52-7 | | 6x+7(x+20)=23+13x-9 | | 8x-2x=10+15 | | 15+d=30 | | 3(4x+12)+4=6(2x-4)+8 | | 8(x+2)-1=5(x+3) | | d−12/14=16 | | 2x−3+3x=12 | | -4x=-2x+2 |